PENGARUH STRES KERJA, BEBAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. DAIYAPLAS SEMARANG - Yang Marcella Devina Santoso; Tristiana Rijanti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to analyze work stress, workload, and work environment on the performance of employees of PT. Daiyaplas Semarang. This sampling method uses a random sample technique and the number of samples in this study is 100 employees. The data used is primary data. Data obtained directly from PT. Daiyaplas Semarang through the questionnaire method. The primary data was then processed and analyzed using SPSS 21. The collected data was then analyzed using multiple linear regression. The results of this study indicate that work stress has a negative and significant effect on performance, workload has a negative and significant effect on employee performance and the work environment has a positive and significant effect on employee performance.